FISH COLLECTED DURING THE CORINDON II AND IV EXPEDITIONS - Fourmanoir, P. (Marine Research in Indonesia, 1984)
The check-list of the fish collected during the CORINDON expeditions (COR. II: 20 sampling stations in the Makassar Strait; COR. IV: 7 stations in Piru and Ambon Bay in the Moluccas) 2) is composed out of 110 species. Most of them are coming from depths between 250 m and 600 m; a dozen of species were found at less deep stations; two Apodes, of which one is the very rare Promyllantor, were collected at a 1000 m depth.